2003
DOI: 10.1124/mol.63.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Resistance Protein (BCRP/ABCG2) Induces Cellular Resistance to HIV-1 Nucleoside Reverse Transcriptase Inhibitors

Abstract: Breast cancer resistance protein (BCRP/ABCG2) is a novel member of ATP-binding cassette transporters, which induce multidrug resistance in cancer cells. We found that a high level of BCRP expression in CD4 ϩ T cells conferred cellular resistance to human immunodeficiency virus type-1 (HIV-1) nucleoside reverse transcriptase inhibitors. The cell line MT-4/DOX 500 was established through the long-term culture of MT-4 cells in the presence of doxorubicin (DOX) and had reduced sensitivity to not only DOX but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 31 publications
1
79
1
Order By: Relevance
“…We have found that ABCG2 can cause resistance to several nucleobase and nucleoside analogues used in cancer chemotherapy in addition to its effect on the antiretroviral nucleosides zidovudine and lamivudine (17,18). Remarkably, ABCG2 transports not only the nucleoside monophosphate metabolite of cladribine-in analogy with other ABC transporters that can cause resistance to nucleobase and nucleoside analogues (6,11,12,14)-but also cladribine itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found that ABCG2 can cause resistance to several nucleobase and nucleoside analogues used in cancer chemotherapy in addition to its effect on the antiretroviral nucleosides zidovudine and lamivudine (17,18). Remarkably, ABCG2 transports not only the nucleoside monophosphate metabolite of cladribine-in analogy with other ABC transporters that can cause resistance to nucleobase and nucleoside analogues (6,11,12,14)-but also cladribine itself.…”
Section: Discussionmentioning
confidence: 99%
“…One other member of this large subfamily of organic anion transporters, ABCC11, is also able to mediate resistance to some nucleobase and nucleoside analogues (16). In addition, several groups recently reported that an ABC transporter from the G family, the ABCG2 (breast cancer resistance protein), is able to cause cellular resistance to various nucleoside analogues, such as the antiretroviral compounds zidovudine, lamivudine (17,18), and PMEA (19) and the antileukemic purine analogue H]2-chloro-2 ¶-deoxyadenosine (cladribine, 2-CdA; ref. 19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simvastatin acid [61] 18 Sulfasalazine [64] 0.6 a Triamcinolone [57] Simvastatin acid [61] Topotecan [57,67,80,84] Ulifloxacin [79] Zidovudine [74] MCT1 L-Lactate [26,88] 4 400/6 000 g-Hydroxybutyrate [26] Nateglinide [89] 187 a D-Lactate [26] Pyruvate [26,88] 2 100/2 500 L-Lactate [26] …”
Section: Substrates and Inhibitorsmentioning
confidence: 99%
“…Chenodeoxycholate-3-sulfate [15] 131 Glycodeoxycholate [15] 2.0 Glycoursodeoxycholate [15] 4.1 Cholate [15,54] [15,54] 7.3/13 Deoxycholate [15,54] 5.2-13 Glycochenodeoxycholate [54] 2.0/2.9 Glychodeoxycholate [54] 2.4/5.4 Glycholate [54] 11/21 Taurochenodeoxycholate [15,54] 1.0-6.1 Taurocholate [15,54] 7.3-25 Taurodeoxycholate [15] 4.5-17 Taurourosdeoxycholate [15] 28 Ursodeoxycholate [15,54] 36 [60] Estrone [56] Bisantrene [67] Betamethasone [57] Riboflavin [68] Taurolithocholate sulfate [56] 37 a Cerivastatin [61] Cerivastain [61] 18 Uric acid [69] Vitamin K3 [ [70] Ciprofloxacin [71] Daunorubicin [56] 59 a Daunorubicin [67] Dexamethasone [57] Diclofenac [72] Diclofenac [72] 71-78 Dipyridamole [73] Digoxin [57] Doxorubicin [67,74] Dipyridamole [73] 6.4 a Enrofloxacin [75] Doxorubicin [56,76] Epirubicin [67] Fluvastatin [61] 5.4 Fluvastatin [61,62] Glibenclamide [77] 150 a Glibenclamide …”
Section: Substrates and Inhibitorsmentioning
confidence: 99%